2008
DOI: 10.1128/jcm.00698-07
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of Methicillin-Resistant Staphylococcus aureus Isolates from Children with Eczematous Atopic Dermatitis Lesions

Abstract: In this study, we investigated the rate of colonization of skin of children with atopic dermatitis (AD) by methicillin-resistant Staphylococcus aureus (MRSA) and characterized the isolates. Active skin lesions in pediatric AD patients were cultured with Rodac Staph (Komed, Korea). S. aureus isolates were examined for drug susceptibilities, analyzed for the eta, etb, tst, and pvl genes, and typed using agr polymorphism, pulsed-field gel electrophoresis of SmaI-restricted chromosomal DNA, and staphylococcal cass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
3
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 40 publications
10
63
3
9
Order By: Relevance
“…A previous report suggested that the detection rate of MRSA from the skin of AD patients was 43.8% in AD inpatients and 29.4% in AD outpatients [34]. Moreover, there has been a report as well that the detection rate of MRSA from pediatric AD outpatients was 18.3% [35]. In this study of AD outpatients, the rate of detection of MRSA was 2.3% (6/261).…”
Section: Discussionmentioning
confidence: 73%
“…A previous report suggested that the detection rate of MRSA from the skin of AD patients was 43.8% in AD inpatients and 29.4% in AD outpatients [34]. Moreover, there has been a report as well that the detection rate of MRSA from pediatric AD outpatients was 18.3% [35]. In this study of AD outpatients, the rate of detection of MRSA was 2.3% (6/261).…”
Section: Discussionmentioning
confidence: 73%
“…4 Kolonisasi MRSA pada individu yang sehat dilaporkan sebanyak 5,1% di Korea Selatan, 4,3% di Jepang, dan 1,9% di Taiwan. 5 Galur MRSA saat ini tidak hanya resisten terhadap metisilin, melainkan memiliki sifat multiresisten terhadap berbagai antibiotik lain yang umum digunakan seperti aminoglikosida, makrolid, kloramfenikol, dan fluorokuinolon, namun istilah MRSA masih digunakan. 4 Seiring ditemukan CA-MRSA di masyarakat, dapat ditemukan pada lesi kulit penderita DA, 5 terutama penderita DA dengan derajat sedang sampai berat.…”
Section: Pendahuluanunclassified
“…Chung dkk. 5 melaporkan MRSA sebanyak 18,4%. Pengobatan lini pertama DA dengan emolien dan kortikosteroid topikal.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…O 16 No Brasil, Moreira e colaboradores avaliaram pacientes com infecção pelo MRSA em um hospital universitário e também encontraram maior número de casos de sepse e mortalidade entre pacientes com bacteremia por MRSA.…”
Section: Mecanismos De Resistência Do S Aureus à Meticilinaunclassified